Dampak Kepercayaan Pelanggan Terhadap Developer Dalam Implementasi Perjanjian Pengadaan Perumahan - Muthia Kayla, Siti; Ainil Muharani; Cantyka Wandira; Helfira Citra (GLOBAL SCIENTS PUBLISHER, 2024)
This study aims to examine the influence of consumer trust levels on developers in implementing housing procurement agreements. Data were obtained through a survey of consumers who have purchased property from various developers. The results of the study indicate that consumer trust levels significantly affect consumer satisfaction with the development process and the quality of the final product. The implication of this study is the importance for developers to build and maintain consumer trust through information transparency, effective communication, and commitment to product and service quality